Screen time: Implications for early childhood cognitive development - Gastaud, Luiza Morrone; Trettim, Jéssica Puchalski; Scholl, Carolina Coelho; Rubin, Bárbara Borges; Coelho, Fernanda Teixeira; Krause, Gabriel Blank; Ferreira, Natasha Mayer; de Matos, Mariana Bonati; Pinheiro, Ricardo Tavares; de Avila Quevedo, Luciana (Early human development, 2023)
Exposure and introduction to digital media, especially in children, are a current cause for concern. The negative links associated with early screen exposure are extensive. To evaluate the association between the time of exposure to a screen in children at 18 months of age and cognitive development in a population-based sample in Southern Brazil. This was a cross-sectional study corresponding to the fourth wave of a population-based cohort study with pregnant women and later, their children living in the city of Pelotas, Southern Brazil. The sample consisted of 470 children who completed the cognitive assessment. Cognitive development was assessed using the Bayley Scales of Infant Development - Third Edition (BSID-III). Exposure to screen time was assessed using a questionnaire completed by the primary caregiver. Of the total, 58.8 % of the children had ≥1 h of screen time per day and the average on the cognitive scale of the entire sample was 96.1 (SD = 14.0). Cognitive development was lower in children whose mothers had lower levels of education (CI 95 % -4.9; −2.1), where boys (CI 95 % 3.2; 8.4) and in children exposed to 2 h or more of screen time/day (CI 95 % -3.6; −0.5). Exposure to screens may have a significant negative association with children's cognitive development and, therefore, we seek to intervene and to give advice to parents and guardians about the true impact of digital media. Further studies are necessary to consolidate the findings and to disclose information on the topic. •The negative effects that accompany the early screen exposure are extensive.•There is a scarcity of studies on the topic in young children.•Cognitive development was associated with lower maternal education and male sex.•Cognitive development was associated with 2 h or more of screen time/day.